Waterways and Development of the Territory: New Mobility and Sustainable Tourism - Giovinazzi, Oriana; Moretti, Marta (TeMA - Journal of Land Use, Mobility and Environment, 2010)
In most cases origin of first urban settlements, waterways have been the main source for human life and the tool for the exchange of goods and cultures. Thanks for their crossing the territory, they have always been places of intersection of different aspects of the urban life bringing together environment, planning, architecture, transport but also art, culture, education and tourism. Due to this aspect, waterways have a great potentiality for the development of a territory with regard to both, mobility – of people and goods – and sustainable tourism. Their regeneration allows to recover a role of public space as rural, urban and tourism landscape of great quality; at the same time, as places for tourism, cultural, gastronomic and leisure uses, they generally induce quality of life. After decades of neglect and indifference, a renewed interest toward the valorization of waterways for culture and tourism is emerging in Italy – particularly in the Nord part of the Country – encouraged also by European directives. Even if with a delay comparing to other European Countries that, since many years, are developing different ways of using waterways, Italy is now showing a new sensibility and approach to look at waterways as an important tool for environmentally sustainable development and to reconnect with a forgotten cultural identity. A selection of projects and initiatives are presented, mostly devoted to the re-launch of water transport for leisure activities and to the rediscover of waterways with a ‘slow’ and ‘soft’ approach. The valorization of architecture, nature and local culture and the proposal of alternative itineraries combining different modalities of transportation are the core of North Italian proposals along the rivers Po, Mincio, Adda, Piave, Limena and the canals network of the Venice lagoon. In particular, the project referred to the Po river, includes the navigation for leisure from Locarno, Switzerland, to Venice, through Milan and the Navigli network. This spectacular trip, every two years realized as a demonstration by the promoting bodies, could be a mid-term goal – at least for part of its length – in view of the Milan Expo 2015: an alternative way of transportation and connection and a tool for the discovery of a less known cultural heritage. Furthermore, the Piave river, in the past main way of communication and witness of many event of the First World War, needs now serious interventions to become more accessible and to be protected from energy production uses. Thanks to the applications of innovative technologies and of new sources of energy, waterways can also act as the best laboratory for sustainable development, at urban and environmental scale. Waterways can represents the chance for a new understanding of urban and natural landscape, in the balance between safeguard and innovation.